Determining the ecotoxicological mode of action of toxic chemicals in meiobenthic marine organisms: stage-specific short tests with Tisbe battagliai - Barata, C. (2013)
A short-term Tisbe battagliai toxicity test design was used to assess the potential ecological effects of pollutants in coastal marine communities. By exposing nauplii and reproductive females over 4 and 6 d, respectively, to 3 toxic substances (fluoranthene, cypermethin and deltamethrin), the bioassay was seen to successfully measure survival effects on egg, nauplii and adults and sublethal effects on food acquisition and clutch size. Predictive consequences of toxic exposure at population level was estimated in terms of reproductive success, by integrating effects on adult survival and reproductive performance over the studied exposure period. Fluoranthene exposure reduced feeding rate and clutch size at concentrations below those affecting survival and population responses. For cypermethrin, survival, sublethal and reproductive success concentration effects were of a similar magnitude. For deltamethrin adult and nauplii survival, clutch size and reproductive success were equally affected at concentrations which were lower than those affecting feeding and egg survival. Responses to contaminated algae showed a different pattern, with toxicant effects only on nauplii survival and reproductive success, and under exposure to pyrethroid insecticides. Thus, differences in the dominant ecotoxicological modes of action, in terms of the balance between survival and sublethal responses with potential effects at the population level, could be successfully assessed using this short-term bioassay. These results have important implications for risk assessment in estuarine and coastal waters because with relatively short-term, and thus cost-effective tests, the functional relationship between effects on survival, feeding and reproduction rates and concentration can be determined.